2006
DOI: 10.1530/eje.1.02109
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and secretion of placental growth hormone around parturition

Abstract: Objective: During pregnancy, placental growth hormone (PGH) is secreted into the maternal circulation, replacing pituitary GH. It is controversial whether PGH levels decline during vaginal birth. After placental expulsion, PGH is eliminated from the maternal blood. GH binding protein (GHBP) and body mass index (BMI) influence GH kinetics, but their impact on PGH kinetics is unknown. The present study was undertaken to define the kinetics of PGH during vaginal delivery and Caesarian section and to relate these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Furthermore, the difference in the mode of delivery between the studied groups probably had no effect on the obtained results. No differences have previously been found in the concentration of hPGH in the maternal blood and the amniotic fluid in respect to caesarean section or vaginal delivery [53,54]. Despite the lack of data regarding the particular genes of this study, it has been shown that gene expression in a near term placenta is not significantly altered by labor, suggesting that the mode of delivery has no major implication in the interpretation of results of genomic studies on placenta [55].…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the difference in the mode of delivery between the studied groups probably had no effect on the obtained results. No differences have previously been found in the concentration of hPGH in the maternal blood and the amniotic fluid in respect to caesarean section or vaginal delivery [53,54]. Despite the lack of data regarding the particular genes of this study, it has been shown that gene expression in a near term placenta is not significantly altered by labor, suggesting that the mode of delivery has no major implication in the interpretation of results of genomic studies on placenta [55].…”
Section: Discussioncontrasting
confidence: 59%
“…The elimination of circulating PGH can be described as the sum of two exponential curves: a rapid elimination phase with a median half-life of 5-6 min, and a slower elimination phase (half-life of 63.4 min) [19] ; thus, 65-89% of plasma PGH is cleared by 30 min after delivery [13,19] .…”
Section: The Placental Growth Hormone Variantmentioning
confidence: 99%
“…The metabolic clearance of endogenous GH-V, estimated following expulsion of the placenta or cesarean section, appears to be somewhat faster than that of 22K-GH [87][88][89][90].…”
Section: Metabolismmentioning
confidence: 89%